2015
DOI: 10.4314/bajopas.v8i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antimicrobial activity of mixed ascorbic acid - nicotinamide metal complexes

Abstract: The present study aimed at synthesizing copper(II) and zinc(II) complexes of mixed ascorbic acid and nicotinamide and physiochemically characterize by solubility test, melting point, conductivity test, infrared, electronic and proton nuclear magnetic resonance techniques. The result of the physiochemical studies indicated 1:1 stoichiometry and were supported by the spectroscopic data. The antimicrobial activities of the mixed complexes were carried out against Bacillus subtilis, Escherichia coli, Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The syntheses and structural elucidations of several mixed ligand complexes of nicotinamide have also been reported (Sahin et al, 2016;Cakir et al, 2001;Ucar et al, 2007, Kose , 2007Al-noor, 2007, Yurdakul et al, 2014. Studies on the antimicrobial activities of the mixed ligand complexes of nicotinamide have shown that the complexes possess higher activity than the free ligands, which is in agreement with numerous reports that have shown that metal complexes of ligands or organic drugs are more active than the free ligands or drugs (Lawal et al, 2015;Akinyele et al, 2020 recorded in the 4000 -400 cm region with a Shimadzu FT-IR 8000 spectrophotometer using KBr pellets. UV-Visible spectra of the samples were measured in the range 800 -200 nm using a Shimadzu UV-Vis 1800 spectrophotometer.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The syntheses and structural elucidations of several mixed ligand complexes of nicotinamide have also been reported (Sahin et al, 2016;Cakir et al, 2001;Ucar et al, 2007, Kose , 2007Al-noor, 2007, Yurdakul et al, 2014. Studies on the antimicrobial activities of the mixed ligand complexes of nicotinamide have shown that the complexes possess higher activity than the free ligands, which is in agreement with numerous reports that have shown that metal complexes of ligands or organic drugs are more active than the free ligands or drugs (Lawal et al, 2015;Akinyele et al, 2020 recorded in the 4000 -400 cm region with a Shimadzu FT-IR 8000 spectrophotometer using KBr pellets. UV-Visible spectra of the samples were measured in the range 800 -200 nm using a Shimadzu UV-Vis 1800 spectrophotometer.…”
Section: Introductionsupporting
confidence: 76%
“…However , the results showed that there was no coordination via the amido group as the frequency of absorption in all the complexes remained unchanged or showed positive shifts which could be as a result of intramolecular hydrogen bonding and other factors. The inability of the ligand to coordinate to nicotinamide via the amido nitrogen is due to the resonance stabilized nature of amides which accounts for their decreased basicity (Lawal et al, 2015). In the same manner, the absorption bands of the C-N remained relatively unchanged.…”
Section: Infrared Spectramentioning
confidence: 99%
“…The ligands bind with the Cu(II) and Hg(II) ions in a bidentate manner through hydroxyl-O and carbonyl -O atoms respectively. Further, the two new bands appeared in the far infrared region at 596-606 cm -1 were assigned to υ(M-N) and υ(M-O) ( Lawal et al 2015). Thus, the IR spectral results provide evidence for bidentate coordination of the two ligands with metal ions.…”
Section: Discussionmentioning
confidence: 79%
“…The molecular weight of this compound is 290.3 g mol −1 [1]. It finds widespread application in treating infections within the urinary tract, respiratory system, and middle ear [2][3], owing to its strong binding to a bacterial enzyme that hinders the creation of tetrahydrofolic acid [4]. Due to its composition of N and O atoms, trimethoprim acts as a multi-dentate ligand, forming comprehensive compounds with metal ions [5].…”
Section: Trimethoprimmentioning
confidence: 99%